Membangun Kompetensi Metakognitif Peserta Didik Melalui Deep Learning Dalam Pembelajaran Pendidikan Agama Islam - Azis, Annisa Rahmania; Tamimi, Abdillah Rosyid (Journal of Research and Thought on Islamic Education (JRTIE), 2025)
Islamic Religious Education continues to face significant challenges in cultivating students’ reflective awareness of religious values. The dominance of textual and memorization-based approaches has hindered the integration of religious teachings into students’ affective and spiritual dimensions. This conceptual study explores how the deep learning approach can foster students’ metacognitive competence in PAI instruction. Drawing on a literature review of educational theories and previous research, the study finds that deep learning strategies—such as reflective discussions, case studies, problem-based learning, self-assessment, and reflective journaling—significantly enhance students’ metacognitive awareness. This enhancement is evident through several indicators: (1) the ability to plan and regulate thinking processes (metacognitive regulation), (2) awareness of personal strengths and weaknesses in understanding religious teachings (self-evaluation), (3) the capacity to connect Islamic concepts with real-life contexts (cognitive-affective integration), and (4) critical reflection on personal religious values and beliefs (value-based awareness). As a result, religious education transforms from mere knowledge transmission into a meaningful process of nurturing self-aware, reflective, and ethically grounded religious character. The study recommends that PAI educators consistently integrate deep learning approaches into instructional design and engage in ongoing pedagogical training to facilitate the development of authentic spiritual awareness through meaningful learning experiences.